2006
DOI: 10.1007/s10029-006-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of laparoscopic and open ventral hernia repairs: a prospective randomized study

Abstract: The laparoscopic approach appears to be as effective as open repairs in the treatment of ventral hernias. Advanced surgical skill, laparoscopic experience and high technology are mandatory factors for successful ventral hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 14 publications
4
116
0
5
Order By: Relevance
“…Although Carbajo et al reported 4 cases with seroma in a 30-patient series [16] and Park et al reported 2 cases with seroma in a 56-patient series [5], in agreement with our study, Reitter et al reported no case with seroma in a 49-patient series [17]. Interestingly, a number of studies reported higher rate of seroma in patients who underwent laparoscopic repair than those who underwent conventional hernia repair [14,18]. We suggest that use of sepramesh in our study prevented dead volume, and, hence, seroma occurrence [19].…”
Section: Discussionsupporting
confidence: 90%
“…Although Carbajo et al reported 4 cases with seroma in a 30-patient series [16] and Park et al reported 2 cases with seroma in a 56-patient series [5], in agreement with our study, Reitter et al reported no case with seroma in a 49-patient series [17]. Interestingly, a number of studies reported higher rate of seroma in patients who underwent laparoscopic repair than those who underwent conventional hernia repair [14,18]. We suggest that use of sepramesh in our study prevented dead volume, and, hence, seroma occurrence [19].…”
Section: Discussionsupporting
confidence: 90%
“…Shorter operative time for laparoscopic incisional hernia repair was reported by a number of recently published studies, 13,14,20,21 while other studies show no differences or longer operative times in the laparoscopic group. 22,23 In small incisional hernia, introduction of trocars and positioning of instruments can be time-consuming. In the open technique, the hernia is often already reduced within this time.…”
Section: Figure-2mentioning
confidence: 99%
“…5 vs 3 days). 13,14,[20][21][22] After laparoscopic surgery, patients are expected to mobilize and recover faster. This, however, could not be confirmed by our data since length of hospital stay was comparable for both groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies revealed that operation time in laparoscopic incisional hernia repair is longer compared to open surgery [12][13][14]. However, there was always a statistically difference in all these studies.…”
Section: Operation Timementioning
confidence: 99%